Effect of Soaking in Shallot (Allium cepa L.) Extract on the Germination of Sengon Buto (Enterolobium cyclocarpum Griseb) Seeds - Elisa Herawati; Agustina Murniyati; Herijanto Thamrin; M. Fadjeri (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
Sengon buto (Enterolobium cyclocarpum) is a long-lived tree species that grows rapidly, is adaptable to various soil types, and is drought-tolerant, making it suitable for land conservation and rehabilitation. This study aimed to determine the effect of seed soaking duration of E. cyclocarpum in shallot (Allium cepa L.) extract on germination percentage, germination rate, and germination power. The research employed a Completely Randomized Design (CRD) with one factor and three treatments (A, B, and C) with 30 replications. The results showed that: (1) there was no significant effect between treatments; (2) germination percentages were: A = 36.66%, B = 40%, C = 13.33%; (3) germination rates were: A = 4.91 (t), B = 5.92 (t), C = 7 (t); (4) germination power: A = 53.33%, B = 73.33%, C = 80%. These results indicate that soaking in A. cepa L. extract did not have a significant effect on the germination parameters of E. cyclocarpum seeds